2017
DOI: 10.4049/jimmunol.1700119
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the Lectin Pathway in the Pathogenesis of Experimental Inflammatory Arthritis: Essential Role of the Lectin Ficolin B and Mannose-Binding Protein–Associated Serine Protease 2

Abstract: Complement plays an important role in the pathogenesis of rheumatoid arthritis (RA). While the alternative pathway (AP) is known to play a key pathogenic role in models of RA, the importance of the lectin pathway (LP) pattern recognition molecules such as ficolin A (FCN A), ficolin B (FCN B) and collectin-11 (CL-11) as well as the activating enzyme MBL (mannose binding lectin)-associated serine protease-2 (MASP-2) are less well understood. We show here that FCN A−/− and CL-11−/− mice are fully susceptible to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…Here, we found that nearly complete silencing of MASP-2 expression by RNAi in the liver using GalNAc-MASP-2-siRNA leads to a partial but significant decrease in the CDA (Figure 3A). These results were consistent with our previous study in which mice lacking MASP-2/sMAp were also partially protected from CAIA (62). Interestingly, we have generated the same phenotype in WT mice as seen in MASP-2/sMAp −/− mice by injecting GalNAc-MASP-2-siRNA duplex, i.e., nearly complete elimination of MASP-2/sMAp proteins in the circulation (Figure 5B).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Here, we found that nearly complete silencing of MASP-2 expression by RNAi in the liver using GalNAc-MASP-2-siRNA leads to a partial but significant decrease in the CDA (Figure 3A). These results were consistent with our previous study in which mice lacking MASP-2/sMAp were also partially protected from CAIA (62). Interestingly, we have generated the same phenotype in WT mice as seen in MASP-2/sMAp −/− mice by injecting GalNAc-MASP-2-siRNA duplex, i.e., nearly complete elimination of MASP-2/sMAp proteins in the circulation (Figure 5B).…”
Section: Discussionsupporting
confidence: 92%
“…The total duration of the CAIA experiment was day 20 post the first siRNA injection. The clinical disease activity (CDA) in all groups of WT mice was determined every day by two trained laboratory personnel acting independently and blinded as to treatment according to our previously published methods (36,40,61,62).…”
Section: Effect Of Galnac-masp-1 and Galnac-masp-2 Duplexes On Inductmentioning
confidence: 99%
“…Interestingly, the anti-inflammatory Siglec-2 has predilection for α2-6 sialic acid, but the pro-inflammatory Siglec-1 binds preferentially to α2-3 50 , thereby supporting our conclusion that pro-inflammatory SFs diminish α2-6 sialylation but not α2-3. Thus, homeostatic α2- 53,54 . These glycan-dependent networks and associated signaling for each sialic acid binding protein could explain the SF-mediated actions to establish chronic inflammation and interactions with immune cells in the arthritic synovium.…”
Section: Discussionmentioning
confidence: 99%
“…The MERS-CoV N protein is thought to interact with mannoseassociated serine protease 2 (MASP2) [32] and translation elongation factor 1 (EF-1A) [33] in the host. Once the mannose-binding lectin recognizes the mannan on the surface of the virus-infected cell, it recruits MASP2 and then activates its enzymatic activity, eventually causing a local or systemic inflammatory response.…”
Section: Modulation Of the Innate Immune Responsementioning
confidence: 99%